Visceral Versus Subcutaneous Adipose Tissue: Immune Microenvironment and Metabolic Consequences - Su, Xinmiao; Li, Hui (Journal of Contemporary Medical Practice, 2026)
The immune microenvironment exhibits significant differences between visceral white adipose tissue (vWAT) and subcutaneous white adipose tissue (sWAT), a disparity that serves as a fundamental mechanism underlying their distinct metabolic outcomes. vWAT is predominantly associated with a pro-inflammatory profile, wherein the release of inflammatory cytokines and free fatty acids (FFAs) promotes insulin resistance (IR) via the portal venous system, thereby contributing to the pathogenesis of type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases (CVDs). Conversely, sWAT is characterized by an anti-inflammatory phenotype and provides a metabolic buffering effect, partially through hyperplastic expansion. Nevertheless, this protective function is compromised when its capacity for expansion is exceeded. A comprehensive analysis of the immune differences characteristic of these two adipose depots, along with an elucidation of the transition from homeostasis to pathological states, will enhance the precise identification of early intervention points for metabolic disorders and offer a theoretical foundation for the development of immune-modulatory strategies targeting specific adipose depots.